TINJAUAN VIKTIMOLOGI TERHADAP TINDAK PIDANA PENGANIAYAAN PEREMPUAN OLEH ANAK LAKI-LAKI DI KOTA PONTIANAK - NIM. A1012211184, DASTOM (Fakultas Hukum Universitas Tanjungpura, 2025)
AbstractBased on preliminary observations made by prospective researchers in Pontianak City, more specifically in the Pontianak City Police (Polresta) Legal Area, it appears that almost every year there is violence against women committed by boys, for example in this year 2024 until September there have been several cases of violence against women. The type of research used in this research is empirical, which is a legal research method that functions to see the law in real terms and examine how the law works in the community. The crime of mistreatment of women committed by boys is due to interpersonal relationship and interaction factors, so that the perpetrators commit acts that violate the criminal law. The discussion of the Contemporary Victimology Theory on the Situated Transaction Model as the basis of this research is in line with the facts in the field, namely in the interpersonal relationships of 2 (two) cases of family relationships, 5 (five) cases of friendly relationships, and 3 (theree) cases of couple relationships. Based on the results of the researcher